Managing Financial Innovations In The Indian Financial Market: Lessons from the UK - Aggarwal, Risha (2011)
India is a developing country and economic development is foremost in its overall growth. Through this research, an important aspect of financial sector, that is, financial innovation is presented. In this research, the existing financial products and the scope for new financial products in an emerging economy like India have been highlighted. A systemic approach to studying various pieces of literature like journal articles, essays, discussion papers and government circulars was adopted with an emphasis on a critical analysis of the same. The aim of the research is to suggest reforms for the inclusion of new products in India. A number of factors like technology, research & development and financial literacy have been deemed necessary for financial evolution. Due to unavailability of information from government bodies and regulators directly, the process of gathering information through secondary research became extensive.